Fostering Inclusivity through Constructivist Learning on AIK Studies for Non-Muslim Students at Muhammadiyah University of Mataram - Palahuddin Palahuddin (STAI Hubbulwathan Duri, 2025)
This study investigates the implementation of a constructivist learning model in Al-Islam and Kemuhammadiyahan (AIK) courses for non-Muslim students at the University of Muhammadiyah Mataram (Ummat). The research addresses how AIK lecturers apply constructivist approaches to promote inclusive and meaningful learning experiences for students from diverse religious backgrounds. A qualitative approach was employed using literature review, direct observation, and in-depth interviews. Data were gathered from five key informants selected through purposive sampling. The analysis followed Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing, with reasoning based on inductive and deductive methods. Findings reveal that AIK instruction for non-Muslim students at Ummat is grounded in an integrative-interconnective paradigm. The application of constructivist learning strategies fosters critical, analytical, collaborative, and communicative skills among students. Moreover, it cultivates values of inclusivity, tolerance, moderation, and peace. These outcomes suggest that constructivist pedagogy not only enhances academic competencies but also contributes to social cohesion in a multicultural educational environment. The study highlights the potential of AIK education to bridge interfaith understanding and reinforce unity in diversity.